A tale of two contaminants: stark differences in the response of N and P to urban lake mitigation efforts. Issue 3 (2nd September 2022) - Cox, Tim; Wolosoff, Steven; Shum, Clifford; Nik-Khah, Taraneh
Abstract: A constructed in-lake water quality mitigation system has proven itself to be effective at reducing Machado Lake phosphorus (P) levels, but ineffective at reducing nitrogen (N) levels. A combination of lake sediment dredging and capping, oxygenation, and a recirculating wetland have reduced lake water column P levels by nearly 50%, as compared to pre-project levels. Key to this result has been the dampening of seasonal P recycling in the sediments. A new lake water quality numerical model is presented, with applications to both pre- and post-project conditions. Model auditing has revealed very good results with respect to predicting mitigation impacts on P but poor results with respect to predicting the performance, or lack thereof, of the N mitigation system. Model sensitivity analyses indicate that the P reductions are primarily attributable to the sediment dredging and capping. Conversely, seasonal data, supported by modeling, suggest that the poor performance of the N mitigation system may be attributable to incomplete removal, or sequestration, of sediment N mass during dredging and/or a lack of impact from the oxygenation system. Future mitigation efforts for the lake should focus on reducing the substantial watershed nutrient loads to the lake and further in-lake P inactivation. HIGHLIGHTS: A new lake water quality model is presented. A major urban lake restoration project is reviewed. Nitrogen and phosphorus mitigation actions are evaluated. Lake mitigation actions include dredging, sediment capping, oxygenation, and recirculating wetlands treatment. This study provides an auditing of both the constructed mitigation system and numerical model predictive power.